Digital transformation of MSMEs in Indonesia: A systematic literature review - Purnomo, Singgih; Nurmalitasari, Nurmalitasari; Nurchim, Nurchim (Nur Science Institute, 2024)
The digital transformation of Micro, Small, and Medium Enterprises (MSMEs) is a crucial driver of economic growth and innovation in Indonesia. This research explores the state of digital transformation among Indonesian MSMEs, focusing on development, digital adoption, and implementation challenges. The method used in this research is a Systematic Literature Review (SLR) with stages: planning, implementation, and reporting. The SLR done in this study utilized a collection of publications published between January 2020 and May 2024. The results of this study show that digital transformation in MSMEs in Indonesia provides significant benefits, such as increased market reach, operational efficiency, and profitability. However, this process faces limited resources, inadequate technical skills, and data security issues. Government support and cooperation with technology providers are essential to overcome these barriers so that MSMEs can optimally utilize digital technology to achieve sustainable growth and higher competitiveness.